Policies to Enhance Prescribing Efficiency in Europe: Findings and Future Implications - Godman, Brian; Shrank, William; Andersen, Morten; Berg, Christian; Bishop, Iain; Burkhardt, Thomas; Garuoliene, Kristina; Herholz, Harald; Joppi, Roberta (Frontiers in Pharmacology, 2011)
Introduction: European countries need to learn from each other to address unsustainable increases in pharmaceutical expenditures. Objective: To assess the influence of the many supply and demand side initiatives introduced across Europe to enhance prescribing efficiency in ambulatory care. As a result provide future guidance to countries. Methods: Cross national retrospective observational study of utilisation (DDDs - Defined Daily Doses) and expenditure (Euros and local currency) of Proton Pump Inhibitors (PPIs) and statins among 19 European countries and regions principally from 2001 to 2007. Demand side measures categorised under the ‘4Es’ – education engineering, economics and enforcement. Results: Instigating supply side initiatives to lower the price of generics combined with demand side measures to enhance their prescribing is important to maximise prescribing efficiency. Just addressing one component will limit potential efficiency gains. The influence of demand side reforms appears additive, with multiple initiatives typically having a greater influence on increasing prescribing efficiency than single measures apart from potentially ‘enforcement’. There are also appreciable differences in expenditure (€/1000 inhabitants/ year) between countries. Countries that have not introduced multiple measures to counteract commercial pressures to enhance the prescribing of generics have seen expenditures up to ten fold or more greater than countries that have instigated multiple demand side measures, although in selected populations. Conclusions: There are considerable opportunities for European countries to enhance their prescribing efficiency, with countries already learning from each other. The 4E methodology allows European countries to concisely capture the range of current demand side measures and plan for the future knowing that initiatives can be additive to further enhance their prescribing efficiency.